Phylogeography of Nasutitermes corniger (Isoptera: Termitidae) in the Neotropical Region. Issue 1 (December 2017) - de Faria Santos, Amanda; Fernandes Carrijo, Tiago; Marques Cancello, Eliana; Coletto Morales-Corrêa e Castro, Adriana
Abstract Background The Neotropical Region is known for its biodiversity and ranks third in number of known termite species. However, biogeographic and phylogeographic information of termites of this region is limited compared to other world geographic regions.Nasutitermes corniger is widely distributed in the region and is of considerable economic importance. The goal of this study was to describe the phylogeography ofN. corniger in the Neotropical Region, to better understand its evolutionary processes. Results The sampled populations ofN. corniger showed high genetic variation. Results indicated strong geographic structure amongN. corniger populations, with most haplotypes not broadly shared among separated locations. Phylogeographic analyses showed a dispersal route forN. corniger from Central America into South America via the Isthmus of Panama, with subsequent dispersal through the highlands east of the Andes and into eastern regions of the continent. The majority of haplotypes were limited in distribution to proximal regions, corresponding to particular biomes (Atlantic Forest, Amazonia, Chaco, Cerrado and Caatinga). Conclusions Nasutitermes corniger is suggested to be a good model for biogeographic and phylogeographic studies in the Neotropical Region. This study clarified the phylogeographic history ofN. corniger and can contribute to the understanding of biogeographic dispersion processes in the Neotropical Region.